ADAM17-Mediated Shedding of Inflammatory Cytokines in Hypertension - de Queiroz, Thyago M.; Lakkappa, Navya; Lazartigues, Eric (Frontiers in Pharmacology, 2020)
The increase of Angiontesin-II (Ang-II), one of the key peptides of the renin-angiotensin system (RAS), and its binding to the Ang-II type 1 receptor (AT1R) during hypertension is a crucial mechanism leading to ADAM17 activation. Among the reported membrane anchored proteins cleaved by ADAM17, immunological cytokines (TNFα, IFN-γ, TGF-β, IL-4, IL-10, IL-13, IL-6R) are the major class of substrates, modulation of which triggers inflammation. The rise in ADAM17 levels has both central and peripheral implications in inflammation-mediated hypertension. This review provides an overview of the functions of ADAM17, with a special focus on its cellular regulation on neuronal and peripheral inflammation-mediated hypertension. Finally, it highlights the importance of ADAM17 to understand the biology of inflammatory cytokines and their role in hypertension.